Pietrele, Rumänien. Reparierte Tongefäße der kupferzeitlichen Siedlung Pietrele (4600–4300 v. Chr.). Ergebnisse der Arbeiten der Jahre bis 2017 - Hansen, Svend (e-Forschungsberichte des DAI, 2018)
Reparation of pottery using drilled holes and string or metal cramps is a widespread practice that has been utilized up until modern times. The considerable amount of pottery in the Copper Age settlement of Pietrele dating from the time between ca. 4600 to 4300/4260 BC enables a relatively precise estimation of how frequently this method of reparation was applied. Of the almost 500,000 sherds and over 2000 largely complete clay vessels, only about 150 sherds or vessels are seen to have drilled holes. Moreover, a number of these drilled holes did not serve mending purposes, but rather to support hanging objects or were used in a later change in the function of the vessel, e.g. into a sieve. One can conclude from this that at no point over the 300-year settlement period of this area was the pottery supply precarious, but rather that broken vessels were normally quickly replaced, therefore ruling out the existence of a special interest in mending pottery.